Killer analytics : top 20 metrics missing from your balance sheet - Brown, Mark Graham. (Wiley and SAS business series, 2013)
"Killer Analytics shows businesses how analytics are being applied to measure components of business performance that traditionally are not measured. New areas include innovation, sustainability, Risk, Project management, and others. The book will show the value of measuring each area and then provide implementation tips. "--